Manufacturing Miracles : Paths of Industrialization in Latin America and East Asia. - Gereffi, Gary; Wyman, Donald L. (Princeton legacy library., 2014)
Few observers of Mexico and Brazil in the 1930s, or South Korea and Taiwan in the mid-1950s, would have predicted that these nations would become economic ""miracles"" several decades later. These newly industrializing countries (NICs) challenge much of our conventional wisdom about economic development and raise important questions about international competitiveness and export success in manufacturing industries. In this volume economists, sociologists, and political scientists seek to explain the growth of the NICs in Latin America and East Asia and to reformulate contemporary developmen